Inverted Internal Limiting Membrane Flap Technique versus Internal Limiting Membrane Peeling for Vitrectomy in Highly Myopic Eyes with Macular Hole-Induced Retinal Detachment: An Updated Meta-Analysis - Ling Ling; Yao Liu; Baixing Zhou; Feifei Gao; Zhe Hu; Man Tian; Yiqiao Xing; Kaibao Ji; Tao Sun; Wentian Zhou (Journal of Ophthalmology)
Background. The aim of this meta-analysis was to compare morphological and functional outcomes between vitrectomy with the inverted internal limiting membrane (ILM) flap technique and vitrectomy with internal limiting membrane peeling in highly myopic eyes with macular hole- (MH-) induced retinal detachment (MHRD). Methods. The PubMed, Web of Science, Embase, and Cochrane Library databases were comprehensively searched from inception to November 10, 2019, for published studies comparing the two techniques for the treatment of MHRD. The outcomes in the collected articles included the postoperative MH closure rate, retinal reattachment rate, and best-corrected visual acuity (BCVA). Review Manager (version 5.3) was used for analyses. Results. In total, seven retrospective studies comparing the inverted ILM flap technique with ILM peeling for the treatment of MHRD were included. The MH closure rate was significantly higher in the inverted ILM flap group than in the ILM peeling group at 6 and 12 months after initial surgery (OR = 15.39; 95% CI: 6.68 to 35.43;P<0.00001 and OR = 12.58, 95% CI: 3.51 to 45.08; P=0.0001), while the retinal reattachment rate was similar in both groups at 6 months after initial surgery (OR = 2.40; 95% CI: 0.89 to 6.50; P=0.08). Besides, the postoperative BCVA was significantly better in the inverted ILM flap group than in the ILM peeling group at 12 months after initial surgery (MD = −0.35; 95% CI: −0.52 to −0.18; P<0.0001). Conclusions. Thus, the MH closure rate and postoperative BCVA may be better with the inverted ILM flap technique than with ILM peeling for myopic MHRD, while the postoperative retinal reattachment rate appears to be similar with both techniques. Therefore, in the future, vitrectomy with the inverted ILM flap technique should be preferred over standard ILM peeling technique for the treatment of MHRD in highly myopic eyes.